Blockchain-enabled supply chain: An experimental study. (October 2019) - Longo, Francesco; Nicoletti, Letizia; Padovano, Antonio; d'Atri, Gianfranco; Forte, Marco
Highlights: There is a lack of studies in the field of blockchain applied to supply chains. Blockchain is used as certification agent for off-chain stored supply chain data. A software connector module connects enterprise information systems with blockchain. A blockchain-enabled supply chain simulation model has been developed. Blockchain fosters collaboration and reduces trust issues in a supply chain. Abstract: Despite Information and Communication Technologies (ICT) have reduced the information asymmetry and increased the degree of interorganizational collaboration, the companies participating a supply chain are less inclined to share data when information is sensible and partners cannot be fully trusted. In such a context, Blockchain is a decentralized certificate authority that may provide economic and operational benefits but companies operating in a supply chain claim to have little knowledge about Blockchain due to its novelty and to the lack of use cases and application studies. In this work, a software connector has been designed and developed to connect an Ethereum-like blockchain with the enterprises' information systems to allow companies to share information with their partners with different levels of visibility and to check data authenticity, integrity and invariability over time through the blockchain, thus building trust. In order to explore the potential of deploying the blockchain in a supply chain, a simulation model has been developed to recreate the supply chain operations and integrated with the blockchain through the same software connector to carry out a scenario statistical analysis. Application results shows how blockchain technology is a convenient instrument to overcome collaboration and trust issues in a supply chain, to increase the supply chain overall performance, to minimize the negative consequences of information asymmetry over the echelons of a supply chain but also to discourage companies from any misconduct (e.g. counterfeiting data or low data accuracy).